1981
DOI: 10.1021/i300001a012
|View full text |Cite
|
Sign up to set email alerts
|

Toluene disproportionation over nickel-loaded aluminum-deficient mordenite. 2. Kinetics

Abstract: A kinetic investigation was conducted for the toluene disproportionation reaction in the presence of a particular zeolite, namely (0.2 wt %) nickel-loaded mordenite with a silica:alumina ratio of 23. Process variables studied were catalyst size, temperature, and contact time. The reaction rate constants calculated on the basis of a reversible second-order reaction model fitted an Arrhenius function of temperature with an apparent activation energy of 14.5 kcal/mol. For the falling rate period, the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The kinetics models in earlier literatures were in great discrepancy. Bhavikatti and Patwardhan observed a reversible second-order reaction model over Ni/mordenite with an activation energy of 14.5 kcal/mol [2]. Bharati and Bhatia observed a single-site adsorption over H-mordenite catalyst [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetics models in earlier literatures were in great discrepancy. Bhavikatti and Patwardhan observed a reversible second-order reaction model over Ni/mordenite with an activation energy of 14.5 kcal/mol [2]. Bharati and Bhatia observed a single-site adsorption over H-mordenite catalyst [5].…”
Section: Resultsmentioning
confidence: 99%
“…Reaction kinetics study has shown to be a crucial research subject for process development, which provides valuable data for reactor design, process optimization, and cycle length prediction. Various kinetic models were proposed for toluene disproportionation (TDP) over several zeolites [2][3][4][5][6][7][8]. Most of the published reports studied mainly on the initial kinetics at low conversion levels and in short onstream time (TOS) with very low coke formation.…”
Section: Introductionmentioning
confidence: 99%
“…The major problem for the commercialization of solid acid catalyzed processes is the rapid deactivation of the catalyst [4,6,7]. Therefore, modeling of the deactivation of the catalyst is a major problem that must be taken into account for the success of such processes.…”
Section: Introductionmentioning
confidence: 99%
“…In these models, however, many simplified conditions have been assumed. Most of these models have been conducted at the laboratory scale under certain conditions with applying no dynamic data [1][2][3][4][5][6][7]12]. Additionally, online investigation of the industrial reactors' parameters (e.g., catalyst deactivation, conversion, product…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In general, mixtures of xylenes can be produced by alkylation of toluene with methanol [6][7][8][9][10][11] or disproportionation of toluene, which produces benzene and xylenes. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The old alkylation process uses AlCl3, 8,27 which is corrosive and associated with tedious disposal problems. Synthetic zeolites have attracted attention as alkylation catalysts owing to their higher acidity, freedom from corrosive substances, potential for regeneration, easy separation from reaction products and elimination of problems associated with disposal of spent catalyst.…”
Section: Introductionmentioning
confidence: 99%